SYNTHESIS, MOLECULAR STRUCTURE AND SPECTROSCOPIC AND COMPUTATIONAL STUDIES ON 4-(2-(2-(2-FORMYLPHENOXY)ETHOXY)ETHOXY)PHTHALONITRILE AS A FUNCTIONALIZED PHTHALONITRILE - Sen, Pinar; Yildiz, Salih Zeki; Atalay, Vildan Enisoglu; Kanmazalp, Sibel Demir; Dege, Necmi (Soc Chemists Technologists Madeconia, 2019)
This work presents the synthesis and characterization of a novel compound, 4-(2-(2-(2-formylphenoxy)ethoxy)ethoxylphthalonitrile as the aldehyde functional group substituted as a phthalonitrile derivative. The spectroscopic properties of the compound were examined through Fourier-transform infrared spectroscopy, Proton nuclear magnetic resonance, Carbon nuclear magnetic resonance, Ultraviolet-visible spectroscopy, Mass spectrometry and elemental analyses. The molecular structure of the compound was also confirmed using X-ray single-crystal data with a theoretical comparative approach.
Keywords: single crystal; aldehyde; phthalonitrile; DFT; HOMO; LUMO